Plasmachemical Synthesis of Composite Nanodispersed Oxides; 3rd Euro-Asian Pulsed Power Conference and 18th International Conference on High Power Particle Beams 2010 (EAPPC/BEAMS 2010), Jeju, Korea, 10-14 October 2010 - Sazonov R. V. Roman Vladimirovich; Kholodnaya G. E. Galina Evgenievna; Ponomarev D. V. Denis Vladimirovich; Remnev G. E. Gennady Efimovich; Razumeyko O. P. Olga Pavlovna (2010, 2010)
В фонде НТБ ТПУ отсутствует